27-9h=-4(5h-2)

Simple and best practice solution for 27-9h=-4(5h-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27-9h=-4(5h-2) equation:


Simplifying
27 + -9h = -4(5h + -2)

Reorder the terms:
27 + -9h = -4(-2 + 5h)
27 + -9h = (-2 * -4 + 5h * -4)
27 + -9h = (8 + -20h)

Solving
27 + -9h = 8 + -20h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '20h' to each side of the equation.
27 + -9h + 20h = 8 + -20h + 20h

Combine like terms: -9h + 20h = 11h
27 + 11h = 8 + -20h + 20h

Combine like terms: -20h + 20h = 0
27 + 11h = 8 + 0
27 + 11h = 8

Add '-27' to each side of the equation.
27 + -27 + 11h = 8 + -27

Combine like terms: 27 + -27 = 0
0 + 11h = 8 + -27
11h = 8 + -27

Combine like terms: 8 + -27 = -19
11h = -19

Divide each side by '11'.
h = -1.727272727

Simplifying
h = -1.727272727

See similar equations:

| 11x=-9 | | 16-7s=9s-20 | | f(x)=x-4/x(x-4) | | 8=8(w-5)+4w | | 2/5x-16=-6 | | 0.675*t^2-2*t+2=0 | | 2(2k+1)x+5(2k+1)y-3k-1=0 | | 1/3(2x-3)3/4(2-4x) | | 20=3(y+4)-7y | | 6x+4=7x-19 | | 1+4u-16=3u-5 | | 2/5x-16= | | 3(v-2)-5v=2 | | x^2-8x^2=9 | | 6(9k-7)=-30 | | 0.675*t^2-2*t=-2 | | 4-(x-5x)=8-2x | | 3a-4=k | | 20x+200=400 | | X/6*4 | | -13k=19-14k | | f/5=8 | | 0=2y-y | | 8/4=/16/x | | 34=6s-8s | | 4c-1=11 | | -12h+13.64=-8.64-13.3h | | -2-19+n=7 | | 3(x+4)=5x-12-2x | | 5+2p-2=7p+27-2p | | 50m+20m+5m=-100 | | 4y+3=x-4 |

Equations solver categories